Roux the day : a dinner club mystery - Wiken, Linda (Wiken, Linda. Dinner club mystery., 2017)
When TV personality Miranda Myers is found dead during a cruise ship casino night, event planner J.J. Tanner is faced with a boatload of suspects, including herself, and turns to her fellow dinner club members to help find clues that could keep her out of hot water. Includes recipes. By the author of Toasting Up Trouble